2012
DOI: 10.1016/j.asjsur.2012.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Recent role of Hassab's operation for cirrhotic patients: Combination with endoscopic procedure for varices

Abstract: Hassab's operation is a satisfactory approach to controlling varices, especially when combined with preoperative endoscopic treatment. Platelet counts were significantly higher after surgery. This therapy was important for cirrhotic patients contraindicated for liver transplantation in that they could continue their therapy for hepatocellular carcinoma (HCC) and HCV as needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…While removal of advanced colorectal neoplasia might be expected to have some effect on incidence, it is difficult to conceive that such an effect would be clearly detectable within 5 years considering the fall in incidence of distal cancers in three of the flexible sigmoidoscopy trials was only just discernible at 5-6 years. [5][6][7] As the authors recognise, ecological analyses are prone to ecological fallacies and confounding from other unrecognised differences between areas. In their analysis, is it possible that there are differences in colorectal incidence and mortality in the early-screening areas and late-screening areas affecting all age groups?…”
mentioning
confidence: 99%
“…While removal of advanced colorectal neoplasia might be expected to have some effect on incidence, it is difficult to conceive that such an effect would be clearly detectable within 5 years considering the fall in incidence of distal cancers in three of the flexible sigmoidoscopy trials was only just discernible at 5-6 years. [5][6][7] As the authors recognise, ecological analyses are prone to ecological fallacies and confounding from other unrecognised differences between areas. In their analysis, is it possible that there are differences in colorectal incidence and mortality in the early-screening areas and late-screening areas affecting all age groups?…”
mentioning
confidence: 99%
“…Particularly, hypersplenism together with collateral circulation is very common in China; elective splenectomy combined with modified Hassab's or Sugiura procedure is thus very popular for portal hypertension in decompensated cirrhosis patients. Meanwhile, previous study indicated surgery a new role for cirrhotic patients as it treated several pathological processes caused by liver cirrhosis [12]. Together with the increasing burden of liver cirrhosis, it is necessary to reevaluate the clinical outcomes of the two procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Bleeding from gastroesophageal varices is a major complication in patients with portal hypertension, especially those with liver cirrhosis, and it may lead to sudden death; the complication is, thus, associated with a high mortality rate. 1,2 Endoscopic procedures, such as endoscopic injection sclerotherapy and endoscopic variceal band ligation, are effective for controlling gastroesophageal varices and are the main methods used presently. 2,3 Radiologic procedures, such as transjugular intrahepatic portosystemic shunt and balloon-occluded retrograde transvenous obliteration (BRTO), are also effective and used for cases wherein the endoscopic procedures were not effective.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Endoscopic procedures, such as endoscopic injection sclerotherapy and endoscopic variceal band ligation, are effective for controlling gastroesophageal varices and are the main methods used presently. 2,3 Radiologic procedures, such as transjugular intrahepatic portosystemic shunt and balloon-occluded retrograde transvenous obliteration (BRTO), are also effective and used for cases wherein the endoscopic procedures were not effective. 2,4,5 The use of surgical treatments has decreased owing to these endoscopic and radiologic procedures, although they are sometimes performed for refractory isolated gastric varices, as surgical operation is the final option for these cases.…”
Section: Introductionmentioning
confidence: 99%